Conditions for acid catalysed luminal nitrosation are maximal at the gastric cardia. Issue 8 (15th July 2003) - Suzuki, H; Iijima, K; Moriya, A; McElroy, K; Scobie, G; Fyfe, V; McColl, K E L
Abstract : Background: Saliva has a high nitrite concentration, derived from the enterosalivary recirculation of dietary nitrate, and is the main source of nitrite entering the acidic stomach. Acidification of nitrite in the presence of secondary amines or amides generates potentially carcinogenic N -nitroso compounds. The reaction is inhibited by ascorbic acid and catalysed by thiocyanate. Aim: To determine whether there is intragastric regional variation in the chemical conditions promoting luminal nitrosation following nitrate ingestion. Methods: Using microdialysis probes, we measured concentrations of nitrite, ascorbic acid, total vitamin C, and thiocyanate simultaneously in saliva, the distal oesophagus, cardia, and the proximal and distal stomach of 17 healthy volunteers before and following intragastric nitrate (2 mmol) administration. Results: The median pH in the distal oesophagus, cardia, and proximal and distal stomach were 7, 2.6, 1.9, and 1.7, respectively, before, and were similar following nitrate administration. Mean nitrite concentration in the distal oesophagus was similar to that of saliva, being 29.1 μM and 36.7 μM, respectively, before nitrate and increasing to 181.6 μM and 203.3 μM after nitrate ingestion. Within the stomach, mean (SEM) nitrite concentration following nitrate was higher in the cardia (45.5 (12.7) μM) than in the mid (7.8 (3.1)) (p<0.01) or distal (0.8 (0.6)) (p<0.1) stomach, and ascorbic acid concentration was lower at the cardia (13.0 (6.1)) than in the mid (51 (19.2)) (p<0.02) or distal (86 (29)) (p<0.01) stomach. Consequently, the median ascorbic acid to nitrite ratio was lowest at the cardia (0.3) (p<0.01) versus the mid (7.8) or distal (40) stomach. Thiocyanate concentration was similar throughout the stomach. Conclusions: The conditions favouring luminal generation of N -nitroso compounds from dietary nitrate are maximal at the most proximal cardia region of the acidic stomach and may contribute to the high incidence of mutagenesis at this site.